The Relationship Between Drivers’ Cognitive Fatigue and Speed Variability During Monotonous Daytime Driving - Ma, Jinfei; Gu, Jiaqi; Jia, Huibin; Yao, Zhuye; Chang, Ruosong (Frontiers in Psychology, 2018)
A lack of task workload can lead to drivers’ cognitive fatigue and vigilance decrement during a prolonged drive. This study examined the effects of speed variability on driving fatigue in a monotonous drive. Twenty-one participants participated in a 60-minute simulated driving task. All participants’ cognitive fatigue was assessed using psychological and physiological measurements. Results showed that among all participants, variability of vehicle speed was negatively correlated with sleepiness and hypo-vigilance during the driving task. Further, drivers in the large variability group reported less sleepiness, less fatigue, and more vigilance than those in the small variability group did during the driving task. These drivers also presented a smaller EEG spectral index (θ+α)/β during the task, where θ, α, and β are the power spectra of three different frequency bands: theta (θ, 4~8 Hz), alpha (α, 8~13 Hz), and beta (β, 13~30 Hz). Our findings suggested that the larger variability of speed within the speed limit may have a deterrent effect on drivers’ cognitive fatigue.